1989
DOI: 10.1021/bi00432a036
|View full text |Cite
|
Sign up to set email alerts
|

Role of the histidine 176 residue in glyceraldehyde-3-phosphate dehydrogenase as probed by site-directed mutagenesis

Abstract: The catalytically essential amino acid, histidine 176, in the active site of Escherichia coli glyceraldehyde-3-phosphate dehydrogenase (GAPDH) has been replaced with an asparagine residue by site-directed mutagenesis. The role of histidine 176 as a chemical activator, enhancing the reactivity of the thiol group of cysteine 149, has been demonstrated, with iodoacetamide as a probe. The esterolytic properties of GAPDH, illustrated by the hydrolysis of p-nitrophenyl acetate, have been also studied. The kinetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 24 publications
3
63
0
1
Order By: Relevance
“…To our knowledge, an esterase activity has been described so far only for the classical glycolytic NAD-dependent GAPDH (44). We found that Synechocystis sp.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…To our knowledge, an esterase activity has been described so far only for the classical glycolytic NAD-dependent GAPDH (44). We found that Synechocystis sp.…”
mentioning
confidence: 68%
“…One unit of enzyme was defined as the amount which catalyzes the generation, or disappearance, of 1 mol of NAD(P)H per min. The esterase activity of GAPDH was determined spectrophotometrically at 30°C by monitoring the p-nitrophenol generated in the hydrolysis of p-nitrophenylesters at 400 nm (44). All kinetic parameters given represent average values of at least four independent determinations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge of the three-dimensional structure will allow us to study, using site-directed mutagenesis, structure-function relationships. A series of mutants affecting amino acids directly related to catalysis or involved in substrate or coenzyme binding have been constructed and characterized (Soukri et al, 1989;Corbier et al, 1990;Corbier, Della Seta & Branlant, 1992, Corbier, Michels, Wonacott & Branlant, 1994. Futhermore, a comparison of the E. coli GAPDH structure with the well refined structure of the B. stearothermophilus GAPDH will help to delineate more precisely the conserved and variable parts of the structure.…”
Section: Introductionmentioning
confidence: 99%